1975
DOI: 10.1083/jcb.64.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Growth of mammalian cells on substrates coated with cellular microexudates. I. Effect on cell growth at low population densities.

Abstract: Mammalian and avian cells cultured on glass or plastic substrates produce microexudates of cellular macromolecules which remain bound to the substrate when the cells are detached. The gross macromolecular composition of microexudates from a range of diploid, heteroploid, and virus-transformed cells was determined with cells labeled with radioisotopes. Significant differences in the amounts of cellular glycoproteins, proteins, and RNA present in microexudates were found between different cell types and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…KEY WORDS substrate glycosaminoglycan LETS glycoprotein microfilament adhesion When normal or SV4(P-transformed murine cells are detached from their tissue culture substrate by treatment with the Ca+*-specific chelating agent EGTA, they leave a small pool of protein and polysaccharide strongly adherent to the substrate, so-called substrate attached material (SAM) (12,36,6,10). SAM is probably similar to the "microexudates" described previously from ellipsometric (37,46,47,31) and electron microscope (34,53) investigations. SAM-coated substrates were subsequently shown to affect the reattachment kinetics (6), the morphological spread and movement (6), and the growth behavior of virustransformed cells (6,47).…”
supporting
confidence: 85%
“…KEY WORDS substrate glycosaminoglycan LETS glycoprotein microfilament adhesion When normal or SV4(P-transformed murine cells are detached from their tissue culture substrate by treatment with the Ca+*-specific chelating agent EGTA, they leave a small pool of protein and polysaccharide strongly adherent to the substrate, so-called substrate attached material (SAM) (12,36,6,10). SAM is probably similar to the "microexudates" described previously from ellipsometric (37,46,47,31) and electron microscope (34,53) investigations. SAM-coated substrates were subsequently shown to affect the reattachment kinetics (6), the morphological spread and movement (6), and the growth behavior of virustransformed cells (6,47).…”
supporting
confidence: 85%
“…This residual "microexudate" is rich in high molecular weight acidic proteoglycans (27). Surfaces coated with microexudate from rapidly proliferating cultures support enhanced growth of cells at low population density, although there is no effect with larger inocula (30,33). Culp (2) has proposed a model in which the negatively charged proteoglycans of the microexudate from the cells bind to the culture surface, which is normally coated with serum proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These glycoproteins are found on the surface of the culture dish on which the cells are grown (Culp and Black, 1972;Poste et al, 1973;Rosenberg, 1960;Weiss et al, 1975;Yaoi and Kanaseki, 1972).…”
mentioning
confidence: 99%
“…Analysis of surface glycoproteins of various human and experimental tumor cells, by a combination of selective radiolabelling and polyacrylamide gel electrophoresis, revealed that neoplastic cells express and shed or secrete different surface glycoprotein patterns depending on cell type, stage of maturation and functional differentiation (Gahmberg et al, 1976;Anderson and Gahmberg, 1978). These glycoproteins are found on the surface of the culture dish on which the cells are grown (Culp and Black, 1972;Poste et al, 1973;Rosenberg, 1960;Weiss et al, 1975;Yaoi and Kanaseki, 1972).…”
mentioning
confidence: 99%